Solid waste management practices in high density suburbs of Zimbabwe: a focus on Budiriro 3, Harare - Nyanzou, P.; Jerie, Steven (Midlands State University, 2015)
The disposal of solid waste is a major environmental challenge in most developing countries including Zimbabwe. Empirical data on people’s perceptions and attitudes towards solid waste and its associated environmental and public health risks are critical for developing sustainable solid waste disposal practices. To date, such empirical information has been lacking, particularly in developing countries such as Zimbabwe. To address this knowledge gap, a case study was conducted in Budiriro, a high-density suburb in Harare. The objective of the present study was to investigate people’s perceptions and attitudes on the nature of solid waste, environmental and health risks associated with solid waste, and waste disposal practices including recycling. To achieve this, structured questionnaires were administered to 156 randomly selected households within the suburb. From this research work, gender, marital status, religion, level of education and age were the main factors influencing peoples’ perceptions and attitudes towards solid waste management. The research findings also revealed that organic solid waste constituted the larger proportion (28%) of the waste generated in Budiriro 3 with a percentage increase of 8.This study further revealed the low levels of knowledge on solid waste disposal technologies among households, and factors motivating solid waste recycling at household level in a typical high-density suburb in Zimbabwe. In the light of these findings, it is recommended that education and awareness need to target changing human attitudes and thinking towards solid waste as the basis for good solid waste management. The study thus provides practical recommendations for solid waste management in high-density suburbs of Zimbabwe and a proposal for further research.